Validity of E-Modules for Teaching Fractions Through Realistic Mathematics Education with The Context of Sacrifice Worship (Ibadah Kurban) - Ikhsan, M; Salsabila, Nada; Johar, Rahmah; Idami, Zahratul; Khairunnisak, Cut; Ellianti, Ellianti; Rossya, Nadila Rizki; Rohaizati, Ulya (Al-Khawarizmi, 2024)
Fraction is one of the difficult topic for students. One way to reduce students’ difficulties is to implement Realistic Mathematics Education (RME) by integrating Islamic values such as Sacrifice Worship (Ibadah Kurban). In addition, the use of technology to integrate sacrificial worship in fraction learning is also expected to increase students' interest in learning in the 21st century and can improve students' understanding. Therefore, it is necessary to develop an e-module for learning fractions through RME with the context of Sacrifice worship. The developed e-module contains learning trajectories, live worksheets, videos, and post-tests. This type of research is research and development which follows the stages of Plomp, especially in the prototyping and assessment stages. The instruments in this study were validation sheets. The validators consisted of one mathematics education lecturer and two Banda Aceh City junior high school teachers. Based on the validity test it was concluded that the e-module meets the valid criteria. The implication of this research is the development of e-modules needs to be continued to test practicality and effectiveness.